Attachment representations in sexually abused preschoolers: a comparative study. Issue 5 (3rd September 2018) - Charest, Florence; Hébert, Martine; Bernier, Annie
ABSTRACT: Attachment theory provides a relevant framework for understanding the psychosocial adjustment of victims of child sexual abuse (CSA). However, most studies have been conducted among adult populations and none have focused on the impact of both preschoolers' and mothers' experience of sexual abuse on attachment security. The aim of this study was to compare attachment representations in sexually abused ( n  = 258) and non-abused preschoolers ( n  = 133), and to explore the relation between maternal history of CSA and children's attachment representations. A story completion task assessing attachment representations was administered to children (Bretherton, Ridgeway, & Cassidy, 1990). The results revealed that CSA preschoolers presented significantly higher levels of attachment disorganization compared to non-abused children, and that abused boys were at particular risk for hyperactivation and disorganization. Associations between mothers' history of CSA and children's attachment representations were non-significant. These findings support the need to consider victims' attachment representations in the implementation of efficient treatment programs. Targeting parent–child relationships in interventions could help promote attachment security in a vulnerable population of preschool victims.